Experimentação do álcool e tabaco entre adolescentes da região Centro-Oeste/Brasil : Pesquisa Nacional de Saúde do Escolar (PeNSE 2015) - Freitas, Elisângela Antônio de Oliveira (2016)
Many health-related behaviors and conditions which underlie major non-communicable chronic diseases begin during adolescence due to inadequate habits of life, such as alcohol and tobacco use. Objective: to investigate the prevalence of alcohol and tobacco experimentation in adolescents of the center- western region of Brazil and its association with sociodemographic factors. Method: School-based cross-sectional study, with data from the National School-based Health Survey – PeNSE carried out in 2015. The sample was composed of 9th year graders from the center-western region/Brazil (n = 14,178). The dependent variable was the experimentation of alcohol and tobacco at some point in life. For the identification of the associated variables, the multiple Poisson regression model with robust variance was performed. The variables with p values inferior to 0.05 (p <0.05) remained in the final model. All analyses were weighted using the statistical package Stata Version 13, since this statistical package makes it possible to incorporate the sampling weights. Results: The estimated prevalence of alcohol and tobacco experimentation was 77.62% and 22.38%. The female gender presented a prevalence rate of alcohol test 6% higher than the boys (p<0.001). This behavior was also statistically significant at the ages of 14 and 15 or more in relation to adolescents up to13 years of age, with a prevalence ratio of 1.15 and 1.42, respectively. Regarding tobacco experimentation, males presented a 15% higher prevalence than females (p <0.001). This behavior was also more frequent in the group age of 14 years or more in relation to those under 13 years of age. The administrative dependence of public schools revealed prevalence17% higher than private schools in tobacco experimentation. Conclusion: Alcohol and tobacco experimentation among school adolescents was shown to be associated with sociodemographic factors. These behaviors in adolescence have implications for the individuals’ well-being and health throughout life.